Enhancement of solar distiller performance by photovoltaic heating system - Omar Badran; Ali Alahmer; Faik A. Hamad; Yousif El-Tous; Ghazi Al-Marahle; Hamed M.A. Al-Ahmadi (International Journal of Thermofluids, 2023)
This study aims to improve the productivity of traditional multi-slope solar stills, which are still employed in isolated villages with no power and no clean drinking water. The conventional multi-slope solar still was equipped with a photovoltaic array system that heated the water through an electric heater submerged in the basin to increase the productivity of the conventional solar stills. This study analyzed and compared the productivity of a PV-coupled solar still (PVSS) with a solar still basin area of 0.64 m2 to that of a conventional solar still (CSS). The results showed that the productivity of the PVSS improved more than triple times (9.39–10.9 L/m2.day) during active mode compared to the CSS, which had a daytime solar still production without a PV system (passive mode) that varied between 2.2–2.34 L/m2.day. The daily efficiency of the passive mode without any additional external energy input was around 27%, which resulted in a distilled water yield of 1.4 L. However, when operated in active mode with supplementary energy inputs, such as electrical heating elements that were powered by solar panels, the daily efficiency of the solar still was approximately 44.8%, resulting in a distilled water yield of 6 liters. The payback period for PVSS was found to be two years. The main observation is that the PVSS has demonstrated its applicability for distillation improvement and a significant increase in production for the entire day when employing a clean energy source.